Association between HIV and blood pressure in adults and role of body weight as a mediator: Cross‐sectional study in Uganda. Issue 11 (12th September 2017) - Okello, Samson; Ueda, Peter; Kanyesigye, Michael; Byaruhanga, Emmanuel; Kiyimba, Achilles; Amanyire, Gideon; Kintu, Alex; Fawzi, Wafaie W.; Muyindike, Winnie R.; Danaei, Goodarz
Abstract : The authors sought to describe the association between human immunodeficiency virus (HIV) and blood pressure (BP) levels, and determined the extent to which this relationship is mediated by body weight in a cross‐sectional study of HIV‐infected and HIV‐uninfected controls matched by age, sex, and neighborhood. Mixed‐effects models were fit to determine the association between HIV and BP and amount of effect of HIV on BP mediated through body mass index. Data were analyzed from 577 HIV‐infected and 538 matched HIV‐uninfected participants. HIV infection was associated with 3.3 mm Hg lower systolic BP (1.2‐5.3 mm Hg), 1.5 mm Hg lower diastolic BP (0.2‐2.9 mm Hg), 0.3 m/s lower pulse wave velocity (0.1‐0.4 mm Hg), and 30% lower odds of hypertension (10%‐50%). Body mass index mediated 25% of the association between HIV and systolic BP. HIV infection was inversely associated with systolic BP, diastolic BP, and pulse wave velocity. Comprehensive community‐based programs to routinely screen for cardiovascular risk factors irrespective of HIV status should be operationalized in HIV‐endemic countries.